PENGARUH KUALITAS PELAYANAN, BRAND IMAGE (CITRA MEREK) DAN TRUST (KEPERCAYAAN) TERHADAP LOYALITAS PELANGGAN PT. POS INDONESIA (PERSERO) KECAMATAN KAPONGAN KABUPATEN SITUBONDO - Mohammad Yahya Arief; Ida Subaida (Growth, 2021)
This study aims 1 to determinethe effectbof service quality, Brand image, and trust partially affect the loyalty of violators 2 to determine the effect of service quality, brand image and trust influence simultaneously on costomer loyalty 3 to find out between service quality, brand image and trust ae the most dominant influence on costomer loyalty. The method uset in this research is quantitative method. The results are multiple linear regression equation Y = 3,550E-17+ 0,214X_1 + 0,213X_2 + 0,510X_3 + e. Partially, service quality has a significant positive effect with a value of 2,732, amouting to 1,663, brand image has a significant positive effect with a value of 2,469, amaoting to 1,663. Trust has a significant positive effect whith a value of 5,721, amouting to 1,663. Simultaneously the quality of service, brand image and trust affect costomer loyalty, whith a value of 26,091, of 2,72. The most dominant variable in this study is must trus with a value of 5,721.